Northwest Pacific ice-rafted debris at 38◦N reveals episodic ice-sheet change in late Quaternary Northeast Siberia - McCarron, Ambrose; Bigg, Grant; Brooks, H.; Leng, M. L.; Marshall, J. D.; Ponomareva, Vera; Portnyagin, M.; Reimer, Paula; Rogerson, M (Earth and Planetary Science Letters, 2020)
The ice-rafted-debris (IRD) record of the open Northwest Pacific points towards the existence of substantial glacial ice on the Northeast Siberian coast during the late Quaternary. However, the scale and timing of glaciation and de-glaciation remains controversial due to the dearth of both onshore and offshore records. Existing IRD data suggests at least one event of dynamic and abrupt change during mid-late Marine Isotope Stage (MIS 3) which mimics the massive collapse of the Laurentide ice sheet during Heinrich Events. It is uncertain whether other events of this magnitude occurred during the late Quaternary. Here we present a ∼160,000yrIRD series, planktic foraminiferal counts and an age model, derived from a benthic δ18O curve, radiocarbon dates and tephrochronology, from core ODP 1207A (37.79◦N, 162.75◦E), revealing the presence of low but episodic flux of IRD. We conclude that glacial Northwest Pacific icebergs spread further south than previously thought, with icebergs emanating from Northeast Siberia being transported to the transition region between the subpolar and subtropical waters, south of the subarctic front during at least the Quaternary’s last two glacial periods. The episodic nature of the 1207A IRD record during the last glacial, combined with coupled climate-iceberg modelling, suggests occasional times of much enhanced ice flux from the Kamchatka-Koryak coast, with other potential sources on the Sea of Okhotsk coast. These findings support the hypothesis of a variable but extensive ice mass during the last glacial over Northeast Siberia, particularly early in the last glacial period, behaving independently of North American and Eurasian ice masses. In strong contrast, IRD was absent during much of the penultimate glacial Marine Isotope Stage (MIS) 6 suggesting the possibility of very different Northeast Siberian ice coverage between the last two glacial periods.